Radiation dose assessment of 64 Multi-Slices Computed Tomography scanner. (January 2021) - Omar, R.S.; Hashim, S.; Ghoshal, S.K.; Bradley, D.A.; Shariff, N.D.
Abstract: This paper reports the performance and dose assessment of the X-ray generator and CT dosimetry of 64 Multi-Slices Computed Tomography (MSCT) scanners operating under the CT scanning condition during the axial mode. The dose was evaluated at various parameters (kV, mA, and exposure time) using a multi-function detector (Unfors) and nanoDot™ optically stimulated luminescence dosimeters (OSLDs). The measured values of the weighted CT Dose Index (CTDIw ) were obtained using a 100 mm standard pencil beam ion chamber and nanoDot™ OSLDs operated on a cylindrical PMMA phantom of 160 mm long (160 mm-diameter head and 320 mm-diameter). The CTDIw values were specified either according to the central axis or 10 mm from the 4 outer edges of the phantom. The two sizes of the phantoms based on the measurements of the CTDIw of the CT scanner were recorded. The values of CTDIw were calculated to determine the performance of the CT X-ray generator. The deviation accuracy of the tube voltage was ±5 kV or ±5% (whichever is greater) whereas the accuracy of the tube potential (mA) was ±10%. The execution of the CT dosimetry steps was shown to ensure patient safety with reduced risk during the improper selection of the dose. It is established that the measured CTDIw values for the radiation dosage under exceptional CT scanning conditions in the axial mode may enable to meet the manufacturer's guidelines (<±20%). Highlights: The performance of an X-ray generator and CT dosimetry of 64 MSCT scanners was evaluated. The X-ray generator and MSCT scanner dose was assessed with different voltage, current and exposure time. The dose was determined accurately using the Unfors and nanoDot™ OSLDs. The nanoDot™ OSLDs were shown to be the right alternatives for the Unfors. Execution of the CT dosimetry steps ensured the patient safety and reduced the risk.